Enhanced recovery pathway after open pancreaticoduodenectomy reduces postoperative length of hospital stay without reducing composite length of stay. Issue 1 (January 2022) - Takchi, Rony; Cos, Heidy; Williams, Gregory A.; Woolsey, Cheryl; Hammill, Chet W.; Fields, Ryan C.; Strasberg, Steven M.; Hawkins, William G.; Sanford, Dominic E.
Abstract: Background/Purpose: There is no data regarding the impact of enhanced recovery pathways (ERP) on composite length of stay (CLOS) after procedures with increased risk of morbidity and mortality, such as pancreaticoduodenectomy. Methods: Patients undergoing open pancreaticoduodenectomy before and after implementation of ERP were prospectively followed for 90 days after surgery and complications were severity graded using the Modified Accordion Grading System. A retrospective analysis of patient outcomes were compared before and after instituting ERP. 1:1 propensity score matching was used to compare ERP patient outcomes to those of matched pre-ERP patients. CLOS is defined as postoperative length of hospital stay (PLOS) plus readmission length of hospital stay within 90 days after surgery. Results: 494 patients underwent open pancreaticoduodenectomy – 359 pre-ERP and 135 ERP. In a 1:1 propensity-score-matched analysis of 110 matched pairs, ERP patients had significantly decreased superficial surgical site infections (5.5% vs 15.5% p = 0.015) and significantly increased rates of urinary retention (29.1% vs 7.3% p < 0.0001) compared to matched pre-ERP patients. However, overall complication rate and 90-day readmission rate were not significantly different between matched groups. Propensity score-matched ERP patients had significantly decreased PLOS (7 days vs 8 days p = 0.046) compared to matched pre-ERP patients, but CLOS was not significantly different (9 days vs 9.5 days p = 0.615). Conclusion: ERP may reduce PLOS but might not impact the total postoperative time spent in the hospital (i.e. CLOS) within 90 days after pancreaticoduodenectomy.